The second-order correction to the ground state energy of the dilute bose gas - Brietzke, Birger; Solovej, Jan Philip (Annales Henri Poincaré, 2020)
We establish the Lee-Huang-Yang formula for the ground state energy of a dilute Bose gas for a broad class of repulsive pair-interactions in 3D as a lower bound. Our result is valid in an appropriate parameter regime of soft potentials and confirms that the Bogoliubov approximation captures the right second-order correction to the ground state energy.
Gesehen am 26.03.2020